Foreign language problmens as a means of building a sense of humour based on the example of German jokes about Turks - Sikorska-Bujnowicz, Katarzyna (Acta Universitatis Lodziensis. Folia Germanica, 2016)
This article attempts to show which incorrect forms used because of foreign language problems are considered to be means of building a sense of humour in German jokes about Turks. Analyses include selected sketches from the Comedy-show “Was guckst du?!” and jokes about Turks from websites.